ANALISIS KOMITMEN DAN KOMPETENSI DAN DAMPAK PADA KINERJA GURU PADA SMAN 1 BANGKINANG KOTA: ANALISIS KOMITMEN DAN KOMPETENSI DAN DAMPAK PADA KINERJA GURU PADA SMAN 1 BANGKINANG KOTA - suarni norawati; robbi abdillah; nurman zakaria (Universitas Lancang Kuning, 2021)
Research to determine the effect of commitment and competence on the teacher performance with simulthan and partial at the SMAN 1 Bangkinang City. Types and sources of data used in this study are primary data and secondary data, while data collection techniques used in this study were questionnaires, file research, observation and interviews. The population in this study were all teachers at the SMAN 1 Bangkinang in 2019, amounting to 54 teachers and all teachers were sampled so that the sampling technique in this research used a saturated census technique. Data analysis was performed using multiple linear regression models. Based on the simulthan test results, the variable of commitment and competence have a significant effect with together on the teacher performance at the SMAN 1 Bangkinang City, while based on the partial test results, the variable of commitment and competence have a significant effect with individual on the teacher performance at the SMAN 1 Bangkinang City. The closeness of the relationship that occurs between the atractiveness of commitment and competence on the teacher at SMAN 1 Bangkinang City performance is very strong with a correlation coefficient R of 87,4%. While contribution of independent variables to the dependent variables is equual to 75,4% while the remaining 24,6% is influenced by other variables not examined in this study.